2009
DOI: 10.2220/biomedres.30.227
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of 4-hydroxynonenal-histidine Michael adduct in the hippocampi of patients with Alzheimer's disease

Abstract: Alzheimer's disease (AD) is among the most common causes of progressive cognitive impairment in humans and is characterized by neurodegeneration in the brain. Lipid peroxidation is thought to play a role in the pathogenesis of AD. 4-hydroxynonenal (HNE) results from peroxidation of polyunsaturated fatty acids and it in turn gives evidence of lipid peroxidation in vivo. HNE reacts with protein histidine residue to form a stable HNE-histidine Michael adduct. To clarify the influence of lipid peroxidation on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…Malondialdehyde (MDA) is a small end product of the degradation of oxidized fatty acids, which can be used as a measure of the LP process. Although MDA and 4-hydroxy-2-nonenal are the major LP products, different fatty acids form specific products -other aldehydes, including oxidized phosphatidylcholine (OxPC), acrolein and isoprostanes during the LP process [7,8]. Free radi cal catalyzed peroxidation of the arachidonic acid, ester ified in membrane phospholipids, transform it into pro staglandinlike, but cyclooxygenase-independent, isoprostanes.…”
Section: Introductionmentioning
confidence: 99%
“…Malondialdehyde (MDA) is a small end product of the degradation of oxidized fatty acids, which can be used as a measure of the LP process. Although MDA and 4-hydroxy-2-nonenal are the major LP products, different fatty acids form specific products -other aldehydes, including oxidized phosphatidylcholine (OxPC), acrolein and isoprostanes during the LP process [7,8]. Free radi cal catalyzed peroxidation of the arachidonic acid, ester ified in membrane phospholipids, transform it into pro staglandinlike, but cyclooxygenase-independent, isoprostanes.…”
Section: Introductionmentioning
confidence: 99%
“…The pathology of AD is dominated by neuronal loss and the formation of amyloid-containing neuritic (senile) plaque and neurofibrillary tangles in the frontal cortex and hippocampus (Zarkovic 2003). Immunoreactive intensity of the HNE-histidine adduct in CA2, CA3 and CA4 sectors in the hippocampi was significantly higher in AD patients than in the controls (Fukuda et al 2009). Strong immunoexpression of acrolein-modified KLH occurred in more than half of the neurofibrillary tangles in AD patients (Calingasan et al 1999).…”
Section: Alzheimer's Diseasementioning
confidence: 89%
“…These results show that pyramidal neurons in these sectors of hippocampi and the neurofibrillary of AD patients are prone to undergo lipid peroxidation. The production of cytotoxic products such as HNE and acrolein may be responsible for the pathogenesis of AD (Fukuda et al 2009). …”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…The indirect evidence of intensive oxidative stress in neuroinflammation are based on tracking concentrations of lipid peroxidation end-products during neuroinflammation (Fukuda et al, 2009;Miller et al, 2011). Some studies of demyelinating plaque have found the increased presence of low-density lipoprotein (LDL) molecules, modified by lipid peroxidation, in the very plaques, macrophages, and astrocytes, in parallel with the increase of the concentration of lipid peroxidation end-products (Hendrickx et al, 2013).…”
Section: Major Findings Disease Model Specimen Referencesmentioning
confidence: 99%